Depreciación de propiedad, planta y equipo en el GAD Municipal del Cantón Vinces en el período 2022. - León Lindao, José Rubén (2023)
The following case study addressed problems consistent with the asset account of property, plant and equipment in the municipal GAD of the canton Vinces during the period 2022. The problem was related to the need to address the issue of asset depreciation. The justification is based on the importance of complying with all relevant regulations when depreciating an asset, considering the management of NICSP 17 within this process. The main objective of the study was to value the assets of the GAD, to then calculate their depreciation and thus establish their fair value. To comply with what was proposed, different methodologies were applied, among which is the interview with the financial department of the GAD. The results revealed that there are shortcomings, which could be solved with an adequate implementation of the NICSP 17 accounting regulations.